Non‐synonymous SNPs in MC1R gene are associated with the extended black variant in domestic ducks (Anas platyrhynchos). (17th May 2012) - Yu, Wenhua; Wang, Cui; Xin, Qingwu; Li, Shijun; Feng, Yanping; Peng, Xiuli; Gong, Yanzhang
Summary In this study, we performed a sequence characterization of the duck melanocortin 1 receptor (alpha‐melanocyte stimulating hormone receptor) (MC1R) gene to analyze the relationship between MC1R polymorphism and the extended black variant in domestic ducks based on the extended black (E) and non‐extended black (e+) allele hypothesis of the duck MC1R gene. Both c.52G>A and c.376G>A substitutions are highly associated with the duck extended black variant (P < 0.01), but the novel c.52G>A substitution is more of a fit for the allele hypothesis of the duck MC1R gene.